The Effect of Tetanus-Diphtheria-Acellular-Pertussis Immunization During Pregnancy on Infant Antibody Responses: Individual-Participant Data Meta-Analysis - Abu-Raya, Bahaa; Maertens, Kirsten; Munoz, Flor M.; Zimmermann, Petra; Curtis, Nigel; Halperin, Scott A.; Rots, Nynke; Barug, Daan; Holder, Beth; Kampmann, Beate; Leuridan, Elke; Sadarangani, Manish (Frontiers in Immunology, 2021)
Background: Immunization with tetanus-diphtheria-acellular pertussis (Tdap) vaccine in pregnancy is increasingly recommended. We determined the effect of Tdap immunization in pregnancy on infants’ vaccine responses. Methods: Individual-participant data meta-analysis of ten studies (n=1884) investigating infants’ antibody response to routine immunizations following Tdap immunization in pregnancy was performed. Geometric mean ratios (GMRs) of antigen-specific immunoglobulin G (IgG) levels were calculated using mixed-effects models. Seroprotection rates were compared using chi-squared tests. Results: Infants of Tdap-immunized women had significantly lower IgG against pertussis toxin (GMR 0.65; 95%CI 0.57-0.74), filamentous haemagglutinin (FHA) (0.68; 0.53-0.87), pertactin (0.65; 0.58-0.72) and fimbria 2/3 (FIM2/3) (0.41; 0.32-0.52) after primary immunization, compared with infants of unimmunized women. These lower levels persisted after booster immunization for FHA (0.72; 0.61-0.84) and FIM2/3 (0.53; 0.29-0.96). After primary immunization, infants of Tdap-immunized women had lower seroprotection rates against diphtheria (90% [843 /973] vs 98% [566/579]; p<0.001) and invasive pneumococcal disease (IPD) caused by 5 Streptococcus pneumoniae (SPN) serotypes (SPN5, SPN6B, SPN9V, SPN19A, SPN23F), and higher seroprotection rates against Haemophilus influenzae type b (short-term and long-term seroprotection rates, 86%[471/547] vs 76%[188/247] and 62%[337/547] vs 49%(121/247), respectively, all p=0.001). After booster immunization, seroprotection rates against diphtheria and tetanus were 99% (286/288) and (618/619) in infants of Tdap-immunized women, respectively. Conclusions: Infants of Tdap-immunized women in pregnancy had lower IgG levels against pertussis, diphtheria and some SPN serotypes after their immunization compared with infants of unimmunized women. Enhanced surveillance of pertussis, diphtheria and IPD in infants is needed to determine the clinical significance of these findings.